Liquid biopsy in non-small cell lung cancer: a meta-analysis of state-of-the-art and future perspectives - Franzi, Sara; Seresini, Gabriele; Borella, Paolo; Raviele, Paola Rafaniello; Bonitta, Gianluca; Croci, Giorgio Alberto; Bareggi, Claudia; Tosi, Davide; Nosotti, Mario; Tabano, Silvia (Frontiers in Genetics, 2023)
To date, tissue biopsy represents the gold standard for characterizing non-small-cell lung cancer (NSCLC), however, the complex architecture of the disease has introduced the need for new investigative approaches, such as liquid biopsy. Indeed, DNA analyzed in liquid biopsy is much more representative of tumour heterogeneity.We performed a meta-analysis of 17 selected papers, to attest to the diagnostic performance of liquid biopsy in identifying EGFR mutations in NSCLC, identifying an overall sensitivity of 0.59, specificity of 0.96 and diagnostic odds ratio of 24,69. Since we noticed a high heterogeneity in the results among different papers, we also performed the meta-analysis in separate subsets of papers, divided by 1) stage of disease, 2) experimental design and 3) method of mutation detection. Liquid biopsy has the highest sensitivity/specificity in high-stage tumours, and prospective studies are more reliable than retrospective ones in terms of sensitivity and specificity, both NGS and PCR-based techniques can be used to detect tumour DNA in liquid biopsy. This is a provisional file, not the final typeset article Overall, liquid biopsy has the potential to help the management of NSCLC, but at present the nonhomogeneous literature data, lack of optimal detection methods, together with relatively high costs make its applicability in routine diagnostics still challenging.